Productive performance, shell quality and internal quality of eggs of quails (Coturnix coturnix) fed with inulin in normal or low calcium diets - Coronado Ibarra, Alejandra (2023)
The aim of this study was to evaluate the effect of adding inulin to diets with normal and low calcium levels on the productive response, shell quality, and internal egg quality in 64 10-week-old laying quail (Coturnix coturnix japonica). The quails were distributed in 4 treatments with 4 repetitions and 4 birds per repetition. The treatments were: T1, basal diet with normal calcium levels (3.16%) without inulin; T2, basal diet with normal calcium levels and with inulin (0.5%); T3, basal diet with low calcium levels (2.37%) and without inulin, and T4, basal diet with low calcium levels and with inulin (0.5%). The experimental period lasted six weeks plus a two-week adaptation period. Feed, in the form of a meal and water were offered ad libitum. Feed consumption and feed conversion were recorded weekly and laying percentage and mortality were done daily. On the last day of the experiment, four eggs were collected for each treatment to evaluate the internal and external quality. The results did not show significant differences between the low calcium with inulin treatment and the normal calcium and inulin treatment, while the calcium level had a significant effect on feed intake. Inulin influenced the egg shape index, being higher with a value of 0.5% inulin. Regarding the internal quality of the egg, lower values were obtained in the yolk diameter with a level of 2.37% of calcium. In conclusion, the addition of 0.5% inulin in low calcium diets obtains production parameters similar to diets with normal calcium levels.